Self-care and clinical parameters in patients with type 2 diabetes mellitus - José Thiago de Sousa; Suyanne Freire de Macêdo; Jayne Ramos Araújo Moura; Ana Roberta Vilarouca da Silva; Eduardo Emanuel Sátiro Vieira; Adriana da Silva dos Reis (Rev Rene)
Objective: to verify characteristics related to self-care and clinical parameters in patients with type 2 diabetes mellitus. Methods: descriptive and exploratory, cross-sectional study, conducted with 173 patients assisted in 12 Family Health Units in the urban area of a city in the Northeast region of Brazil. Results: most participants (61.3%) were female, aged less than 60 years old. There were significant differences in the lower glycemic control (p = 0.014), capillary glycemia (p = 0.018) and alcohol consumption (p = 0.015) for men as well as higher central obesity indexes for women (p = 0.000). It was observed high frequency of overweight, abdominal obesity, high blood pressure, elevated blood glucose levels and insufficient levels of physical activity. Conclusion: there is the need for nursing actions aimed at improving self-care and control of the clinical parameters in these patients.